ANALISA FAKTOR YANG MEMPENGARUHI AUDIT DELAY PADA PERUSAHAAN PERTAMBANGAN PERIODE 2017-2021 (Lembaga Pengembangan Kinerja Dosen, 2022)
This study aims to analyze the effect of profitability, leverage and audit committee on audit delay. This research was conducted on mining companies listed on the Indonesia Stock Exchange (IDX) for the 2017-2021 period. The sample in this study was obtained by using a purposive sampling method, namely the sampling technique based on certain criteria. The results of this study conclude that (1) profitability has a negative effect on audit delay, (2) leverage has a positive effect on audit delay, while (3) audit committee has a negative effect on audit delay.